NILAI BUDAYA PADA LANSKAP INDUSTRI PERKEBUNAN KINA CINYIRUAN BANDUNG PADA MASA KOLONIAL - Lia Nuralia; Iim Imadudin (Patanjala: Journal of Historical and Cultural Research, 2021)
Perkebunan Kina Cinyiruan di Bandung telah berdiri sejak tahun 1855. Sekarang ini telah menjadi kebun afdeeling dari Perkebunan Kertamanah PTPN VIII, sejak digabungkan secara manajerial di masa kemerdekaan. Jejaknya dapat ditelusuri sebagai lanskap budaya industri perkebunan berupa area bekas kebun kina dan permukiman emplasemen, yang mengandung nilai budaya. Apa dan bagaimana nilai budaya tersebut menjadi permasalahan pokok dalam tulisan ini. Metode penelitian adalah desk research dengan pendekatan arkeologi industri serta konsep nilai budaya dan lanskap budaya. Hasil yang diperoleh adalah lanskap budaya industri Perkebunan Kina Cinyiruan memiliki tata guna lahan beragam dengan tinggalan budaya benda beraneka fungsi. Nilai budaya yang terkandung di dalamnya merupakan nilai budaya tradisional Sunda dan nilai budaya kolonial, terkait kearifan lokal dan teknologi modern barat. Kedua nilai budaya tersebut tampak pada tata letak dan arsitektur bangunan permukiman, serta tata guna lahan area kebun sebagai sistem ekonomi subsistensi dan perkebunan sebagai sistem ekonomi modern Barat yang komersial.The Cinyiruan quinine plantation in Bandung has been established since 1855. After the managerial merger during the independence of Indonesia, it is now the government-owned plantation of PTPN VIII Kertamanah. The existence of the plantation can be traced as a cultural landscape of the plantation industry. It includes the area of the former quinine plantation and the emplacement settlement. Both contain cultural values. The main problem in this paper comprise what and how the values are. The research method used is the desk research with an industrial archeology approach and the concept of cultural values and cultural landscapes. The results obtained indicate that the cultural landscape of the Cinyiruan quinine plantation industry has a variety of land uses with cultural relics of various functions. The cultural values contained are the Sundanese traditional cultural values and colonial cultural values which relate to the local wisdom and western modern technology. These two cultural values are traceable in the layout and architecture of residential buildings as well as the land use of the garden area as a subsistence economic system and the plantations as a modern commercial Western economic system.